Penerapan Model Kooperatif Numbered Head Together Berbantuan Papan Refusi untuk Meningkatkan Pemahaman Konsep Matematis Siswa: Penelitian - Intan Rambu Kahi Timbang; Darius Imanuel Wadu; Iona Lisa Ndakularak (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The application of the Numbered Head Together (NHT) type cooperative model with refusi board media at SMP Negeri 1 Umbu Ratu Nggay Tengah aims to improve students' understanding of mathematical concepts. The research method used was Classroom Action Research (PTK) involving 31 students. Research data collection techniques use written test techniques and observation techniques, with data analyzed using descriptive statistical analysis methods. The results showed a significant increase with the percentage of success in pre-cycle students' comprehension ability of 6%, increasing by 23% in cycle I, then increasing to 77% in cycle II. Thus, it can be concluded that the application of the Numbered Head Together (NHT) type cooperative learning model with refusi board media can improve students' understanding of mathematical concepts.